1999
DOI: 10.1007/s100510050820
|View full text |Cite
|
Sign up to set email alerts
|

Can one hear the shape of an electrode? II. Theoretical study of the Laplacian transfer

Abstract: The flux across resistive irregular interfaces driven by a force deriving from a Laplacian potential is computed on a rigorous basis. The theory permits one to relate the size of the active zone Aact. to the derivative of the spectroscopic impedance Zspect.(r) with respect to the surface resistivity r through:. It is shown that the macroscopic transfer properties through a system of arbitrary shape are determined by the characteristics of a first-passage interface-interface random walk operator. More precisely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 5 publications
1
76
0
Order By: Relevance
“…[10] brings the relaxation length D/K which is the distance a particle should travel near the boundary before surface relaxation effects reduce its expected magnetization. The relaxation length is also called ''unscreened perimeter length'' and it plays an important role in diffusive transport phenomena (10,11,(18)(19)(20)(21)(22)(23)(24). The third dimensionless variable…”
Section: Length Scales and Dimensionless Parametersmentioning
confidence: 99%
“…[10] brings the relaxation length D/K which is the distance a particle should travel near the boundary before surface relaxation effects reduce its expected magnetization. The relaxation length is also called ''unscreened perimeter length'' and it plays an important role in diffusive transport phenomena (10,11,(18)(19)(20)(21)(22)(23)(24). The third dimensionless variable…”
Section: Length Scales and Dimensionless Parametersmentioning
confidence: 99%
“…Halsey first indicated that the response of such systems depends on the probability that a particle starting on the interface comes back to it [5]. Generalizing these ideas, it has been recently shown that the Laplacian transfer across irregular interfaces is controlled by a single linear operatorQ which maps the static surface onto itself through effective "Brownian bridges" [6]. In this context, each surface has an operatorQ, which is symmetric and positive.…”
mentioning
confidence: 99%
“…It is also interesting to return to the exact concept of the self-transport operator attached to a given morphology [6]. Extending the notion of diffusive self-transport in this context, it might be that DRA shapes could be considered as "eigenshapes" of these operators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, they showed that the frequential behavior of a rough electrode could be obtained by studying the spectral properties of the so-called self-transport operator [5,6]. The latter measures the probability for two given sites of an interface to be linked by random walk through the electrolyte.…”
Section: Introductionmentioning
confidence: 99%